Collaborative Governance dalam Tata Kelola PDAM (Studi Kasus: Cluster Perumahan di Probolinggo) - Isna Wardhatul Khumairoh; Nourma Ulfa Kumala Devi; Sigid Widyantoro (Lembaga Yasin AlSys, 2025)
The availability of clean water remains a significant challenge in various Indonesian cities, including Probolinggo. Although Probolinggo City Regulation No. 5 of 2014 mandates the use of clean water services provided by the local water utility (PDAM) in residential area development, its implementation has yet to be fully effective. This study aims to analyze the collaborative governance strategy in the management of Perumdam Bayuangga in residential areas, as well as to identify the obstacles and efforts of stakeholders in implementing the policy. A descriptive qualitative approach was employed, with data collected through interviews, observations, and document analysis. The findings indicate that collaboration among the PDAM, government, and developers has improved, but remains unsystematic and lacks sustainability. Interactions among actors tend to be reactive, with no regular official forum in place. Moreover, community participation as end users is still passive and suboptimal. Nevertheless, Perumdam Bayuangga demonstrates a prompt response to public complaints. The study concludes that the effectiveness of collaboration is largely influenced by an adaptive institutional design, facilitative leadership, and proportional involvement of both primary and secondary stakeholders. These findings offer practical contributions to the enhancement of public service governance and may serve as a reference for similar policy development in other regions facing clean water access challenges.